Life of a Ti–6Al–4V alloy under fretting fatigue: Study of new nonlocal parameters. (April 2017) - Ferry, Barbara; Araújo, José Alexander; Pommier, Sylvie; Demmou, Karim
Abstract: This paper proposes the experimental validation of a nonlocal method which describes the stress gradient effect in fretting fatigue. Through the extraction of an approximate velocity field at the proximity of the contact edge, it has been possible to extract nonlocal intensity factors that take into account the gradient effect, whatever the geometry considered. A multiaxial fatigue criterion, the Multiaxial Wölher Curve Method in conjunction with the Theory of Critical Distance, was applied in terms of nonlocal intensity factors not only to predict the boundary between the safe zone and the damage zone, but also to estimate the number of cycles to failure. To validate the reliability of this nonlocal description, a set of fretting experiments was conducted for a Ti–6Al–4V alloy. These experimental tests were carried out by varying the stress gradient at the vicinity of the contact. Highlights: The use of nonlocal index to predict fretting fatigue life of system is proposed. The Modified Wölher Curve Method was applied with the nonlocal index. Experimental validation were done with a bi-axial MTS. Nonlocal map was draw for titanium alloy. Results showed good predictions for the identification of failure's boundary.